DIFFERENCES IN SOCIAL STRATIFICATION COMMUNITY PERCEPTIONS OF POST-TRUTH MANAGEMENT - Aji Yoga Sekar; Marwan, Jubery (Universitas prof. Dr. Moestopo (Beragama), 2025)
The post-truth phenomenon that is developing in society is having very powerful social impacts. Many lower levels of society believe in information that seems to be true, but is not supported by sufficient evidence and relative facts. The emergence of information that is not balanced with the reality of what is happening makes all groups consisting of; among students/akademics, entrepreneur, and the public in responden to the post-truth phenomenon in social life. The reasearch is aim at how society manages post-truth correctly and in a balanced manner. This research is included in the category of explanatory research, which uses hypoteses (hypothesis testing). The data sources used are nominal and primary data obtained through distributing questionnaires using a likert scale. Sampling was carried out using a purposive sampling model with certain criteria based on the sosial strata of the community, totaling 180 respondents. Dat analysis uses multivariate variance (Manova). The risearch results show that: 1) student, entrepreneurs, and public can manage post-truth by thinking critically, understanding digital literacy, and knowing social media algoritms well and wisely; 2) There is a significant difference in perspective between them (students, entrepreneurs, and public) regarding good and wise post-truth management.